COVID‐19 antibody positivity over time and pregnancy outcomes in seven low‐and‐middle‐income countries: A prospective, observational study of the Global Network for Women's and Children's Health Research. (2nd January 2023) - Goldenberg, Robert L.; Saleem, Sarah; Billah, Sk Masum; Kim, Jean; Moore, Janet L.; Ghanchi, Najia Karim; Haque, Rashidul; Figueroa, Lester; Ayala, Alejandra; Lokangaka, Adrien; Tshefu, Antoinette; Goudar, Shivaprasad S.; et al.
Abstract: Objectives: To determine COVID‐19 antibody positivity rates over time and relationships to pregnancy outcomes in low‐ and middle‐income countries (LMICs). Design: With COVID‐19 antibody positivity at delivery as the exposure, we performed a prospective, observational cohort study in seven LMICs during the early COVID‐19 pandemic. Setting: The study was conducted among women in the Global Network for Women's and Children's Health's Maternal and Newborn Health Registry (MNHR), a prospective, population‐based study in Kenya, Zambia, the Democratic Republic of the Congo (DRC), Bangladesh, Pakistan, India (two sites), and Guatemala. Population: Pregnant women enrolled in an ongoing pregnancy registry at study sites. Methods: From October 2020 to October 2021, standardised COVID‐19 antibody testing was performed at delivery among women enrolled in MNHR. Trained staff masked to COVID‐19 status obtained pregnancy outcomes, which were then compared with COVID‐19 antibody results. Main Outcome Measures: Antibody status, stillbirth, neonatal mortality, maternal mortality and morbidity. Results: At delivery, 26.0% of women were COVID‐19 antibody positive. Positivity increased over the four time periods across all sites: 13.8%, 15.4%, 21.0% and 40.9%. In the final period, positivity rates were: DRC 27.0%, Kenya 33.1%, Pakistan 32.8%, Guatemala 37.0%, Zambia 37.8%, Bangladesh 47.2%, Nagpur, India 57.4% and Belagavi, India 62.4%. Adjusting for site and maternal characteristics, stillbirth, neonatal mortality, low birthweight and preterm birth were not significantly associated with COVID‐19. The adjusted relative risk (aRR) for stillbirth was 1.27 (95% CI 0.95–1.69). Postpartum haemorrhage was associated with antibody positivity (aRR 1.44; 95% CI 1.01–2.07). Conclusions: In pregnant populations in LMICs, COVID‐19 antibody positivity has increased. However, most adverse pregnancy outcomes were not significantly associated with antibody positivity.